Boosting Students' Representation Ability in Mathematics Using Numbered Heads Together - Nuritasari, Fetty; Qomariyah, Lailatul; Agustin, Dayriqoh; Mulkis, Ismi Malika; Zayyadi, Moh (Journal of Educational Management and Learning, 2023)
This study aims to examine the efficacy of the Numbered Heads Together learning model in enhancing students' proficiency in whole number calculations. Utilizing a classroom action research methodology, the research was structured into two main cycles, preceded by an initial pre-cycle phase. Each cycle comprises four phases: planning, acting, observing, and reflecting. Data were primarily collected through tests, complemented by student interviews to enrich the test findings. The gathered data were processed and analyzed using qualitative descriptive methods. The participants were nine fifth-grade students from SDN Panglegur 1 Pamekasan, Madura, Indonesia who had previously engaged with integer arithmetic operations. The findings reveal that the Numbered Heads Together model not only significantly improved students' academic performance but also positively influenced their engagement, responsibility, discipline, and confidence in interactive learning scenarios. This improvement was evident from the pre-cycle phase through to the second cycle, with student performance increasing from 33% in the pre-cycle to 56% in the first cycle, and further to 78% in the second cycle.